A geographic distribution of selected lexical variants in Ilocano vocabulary - Navarro, Emma Llanes 1946-
The study describes the geographic distribution of twenty-five selected lexical variants in Ilocano vocabulary as spoken in Sta. Cruz, Sta. Maria, and Magsingal in Ilocos Sur, and Sarrat, Bacarra, and Bagui in Ilocos Norte. The paper is primarily concerned in finding the differences in forms of words having similar meanings. The study is based on the premise that change is one characteristic of language, and that geogprahic variations exist in either the pronunciation, structure, or lexicon of a language.